Teste dicótico de sentenças em português brasileiro em adolescentes normo-ouvinte - Muller, Maryndia Diehl (2019)
This study aimed to investigate the applicability and performance of normal hearing adolescents with the new Dichotic Sentence Identification Test in Brazilian Portuguese in the free and directed attention stages, according to gender and ear side variables. The sample was composed of 28 subjects, 20 women and 8 men, aged between 12 and 17 years of age, with mean age of 15:8 years. A audiological basic assessment and the Dichotic Digits Test were established as inclusion criteria. To evaluate the dichotic listening was used for Brazilian Portuguese Dichotic Sentence Identification Test of 50 dB NS, investigating the performance the free and directed attention stages. The adolescents were able to understand and perform the tasks proposed by the Dichotic Sentence Identification Test in Brazilian Portuguese. There was no statistically significant difference regarding gender. In the free attention stage, the average performance of the right was 93.93% and the left 84.64%. It was considered as a cutoff point for the right ear 90% of correct answers and for the left ear 80%, with a statistically significant difference between the ears. The asymmetry between the ears considered expected for this population was up to 10%, with the advantage of the right ear. In the directed attention stage, the average performance was approximately 99%, and the expected value in this task was 100%, in both ears, for this population. It was verified the applicability of the new proposed test in the evaluated population. Data showed asymmetry according to the ear side in the free attention stage, with the advantage of the right ear.